2023
DOI: 10.1111/jfd.13792
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genome analyses of three serotypes of Lactococcus bacteria isolated from diseased cultured striped jack (Pseudocaranx dentex)

Abstract: Lactococcosis, caused by members of the genus Lactococcus, represents a devastating disease inducing mass mortalities and economic losses in many fish species worldwide. The present work aimed to compare the whole genome sequences of three different serotypes of Lactococcus garvieae isolated from diseased cultured striped jack (Pseudocaranx dentex) in Ehime prefecture, Japan. The three serotypes showed different virulence in the challenge test using Japanese amberjack (Seriola quinqueradiata). The genome seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Fragments measuring 285 bp correspond to serotype I, while fragments measuring 1,285 bp correspond to serotype II [15]. Using this methodology, serotype I was detected in diseased Anguilla anguilla, Oncorhynchus mykiss, Paralichthys olivaceus, Pseudocaranx dentex, Rachycentron canadum, Seriola quinqueradiata, Seriola dumerili, and Trachinotus blochii [15,16,25,[47][48][49]. On the other hand, serotype II was detected in Pseudocaranx dentex, Seriola quinqueradiata, Seriola dumerili and Seriola lalandi [15,50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fragments measuring 285 bp correspond to serotype I, while fragments measuring 1,285 bp correspond to serotype II [15]. Using this methodology, serotype I was detected in diseased Anguilla anguilla, Oncorhynchus mykiss, Paralichthys olivaceus, Pseudocaranx dentex, Rachycentron canadum, Seriola quinqueradiata, Seriola dumerili, and Trachinotus blochii [15,16,25,[47][48][49]. On the other hand, serotype II was detected in Pseudocaranx dentex, Seriola quinqueradiata, Seriola dumerili and Seriola lalandi [15,50].…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that L. garvieae and L. petauri strains were classified as serotype I, while the isolates of L. formosensis were characterized as serotype II (Figure 2). In addition, one isolate that was previously classified as serotype II [50] was recently described as belonging to L. formosensis [47]. Furthermore, we performed an in silico PCR, using java web tools [51], for all the complete genomes (I4/60, GenBank accession number: GCA_023822125.1; 122061, GCA_002355575.1; and MS200408A, GCA_030295725.1) and the reference genome (NBRC 109475, GCA_018403745.1) of L. formosensis strains, with taxonomy checked on the NCBI database, and also found an expected PCR product size of 1,285 bp.…”
Section: Discussionmentioning
confidence: 99%